Water Level Intelligent System of Data Acquisition and Early Warning - Lei Li; Fenglian Cao; Zheng Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to improve work efficiency of hydrometric station, guarantee the accuracy and timeliness of water level data acquisition, process water level data in a timely manner and make early warning of risk, mobile devices are proposed as collection, sending and early warning terminal of water level data, and the upper computer as the receiving and processing terminal of water level data. The water level access algorithm is studied, and the stripping method is used to obtain the high-accuracy water level information. The image thinning algorithm is applied to optimize, so as to reduce the complexity of the algorithm. The programming is able to control real-time data sending, which realizes the data exchange between server terminal and communication module. Microsoft Access database is applied to the operation of water level information and the design of man-machine interface. Experimental study shows that this system can accurately acquire information in real time, undertake statistical analysis of data with many functions such as early warning, effectively improve the work efficiency of water level monitoring and improve the management level of hydrological industry. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5450